Solar Panel Charger Batery - Ferdiansyah, Riko; Putra, Dimas Nur Arif Dwi; Nafi, Ahmad Dhiyaun; Tamam, Badrut (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This paper reviews the design and implementation of a battery charger that utilizes renewable energy sources, especially solar energy. The main emphasis of this research lies on the effectiveness of battery charging, the monitoring system to check the state of charge, as well as the protection inside the battery to extend its lifespan. By utilizing solar panel technology, the system is designed to offer an environmentally friendly and sustainable solution to the battery charging process. The findings of this study show that the developed system can achieve a maximum level of charging efficiency, as well as features that ensure safety and reliability during use.